Taurine synthesis in teleost-importance of cysteamine pathway - Haga, Yutaka; Mojena Gonzales, Maria; Kondo, Hidehiro; Hirono, Ikuo; Satoh, Shuichi (Facultad de Ciencias Biologicas, 2017)
Taurine plays various roles in animals such as growth promotion, osmoregulation, bile acid conjugation,neurotransmission, cardiac muscle contraction, antioxidant activity, and reproduction. Taurine is one of theessential nutrients for marine fish larvae and in fishes which lack endogenous taurine production. Taurine issynthesized from methionine via cysteine. Cysteine is converted to cysteine sulfinic acid by activity of cysteinedioxygenase (CDO) and cysteine sulfinic acid is converted into hypotaurine by cysteine sulfinic aciddecarboxylase (CSD) in CSD pathway which is considered to be a major taurine production pathway in fish.Hypotaurine is finally converted into taurine by auto-oxidation. In addition to CSD pathway, there is two othertaurine synthetic pathways are know: cysteic acid pathway where cysteine is oxidized into cysteic acid, and it isdirectly converted into taurine by cysteic acid decarboxylase (CAD) activity and cysteamine pathway wherecysteine is converted into cysteamine and it is converted into hypotaurine by cysteamine dioxygenase (ADO).However, detail on taurine production by these two pathways is not understood.Common carp is widely cultured in the world and world production of cypriniforms is highest among food fishspecies. Rainbow trout is known to have sufficient CSD activity to produce taurine via methionine. In contrast,it was reported that CSD activity in common carp is about half of that reported in rainbow trout. However,common carp did not show growth retardation when it was fed taurine deficient diet. These observations led265Haga, Y. et al., 2017.Taurine synthesis in teleosts-importance of cysteamine pathway. En: Cruz-Suárez, L.E., Ricque-Marie, D., Tapia-Salazar, M., Nieto-López, M.G.,Villarreal-Cavazos, D. A., Gamboa-Delgado, J., López Acuña, L.M. y Galaviz-Espinoza, M. . (Eds), Investigación y Desarrollo en Nutrición Acuícola Universidad Autónoma de NuevoLeón, San Nicolás de los Garza, Nuevo León, México, pp. 264-283. ISBN 978-607-27-0822-8.hypothesis that common carp is able to produce sufficient amount of taurine beside the CSD pathway. Thepurpose of the present study is to investigate effect of dietary supplementation of cysteine, cysteamine,methionine, and taurine on the growth, sulfur amino acid content, and gene expression of taurine synthesizingenzymes.Eight different diets supplemented with taurine, methionine, cysteine, and cysteamine were fed to the juvenilecommon carps for 30 days. For control, a diet without supplying sulfur amino acid was fed. Feeding dietssupplemented sulfur amino acid resulted in better survival, growth, feed conversion ratio, and protein efficiencyratio except treatments supplemented with cysteamine. It was observed that the supplementation of dietarycysteamine caused growth retardation, myopathy, and body deformity in common carp. All sulfur amino acidsincreased taurine deposition in the carcass and 1.5% cysteamine increased taurine deposition by 1.8 and 5.5times higher than those of the methionine and cysteine treatments. CDO was tended to be down-regulated bycysteine and low dose of taurine but up-regulated by a high dose of cysteamine. It was observed that CSD wasdown-regulated by sulfur amino acids. ADO was down-regulated by methionine, cysteine and low dose oftaurine but up-regulated by cysteamine.These results suggest that CSD pathway plays a role in taurine synthesis and cysteamine pathway is anothermajor taurine synthesizing pathway in common carp.